Do lago do segredo ao segredo da escola: experimentações formativas no ensino de ciências em diálogos com a tradição - ROCHA, Nádia Sueli Araújo da (Universidade Federal do Pará, 2022)
Whereas the sociocultural relevance of the traditional knowledge in the context of the Segredinho community belonging to the Municipality of Capanema in the Pará State of the northeast Pará, it is the object of the present study from the knowledge related to artisanal fishing and the myth originated in Segredo Lake, environment natural, which adds science, culture, and history. The composition of these elements gave rise to the following research question: how are the relationships between traditional knowledge and scientific knowledge configured in Science Teaching at the school of the Segredinho community? Taking into account that the dialogical relations between traditional and scientific knowledge are fundamental for Science Teaching based on the diversity and multidimensionality of knowledge. Thus, this thesis aimed to understand the relationship between scientific knowledge and the traditional knowledge of the Segredinho community in Science Teaching, considering a view to the formation of teachers in the perspective of the dialogue between this knowledge. In order to understand these relationships, this study was supported in qualitative research in the form of action research in which six (06) residents, three (03) teachers from the community school, who worked in the early years of Elementary School were involved in the multi-series modality and two (02) school students. Science Teaching was perceived through the transmission of content, the lack of articulation with the knowledge of tradition, and the memorization of didactic concepts. After analyzing and problematizing the teaching practice carried out at the community school were formative meetings were developed with the teacher 4th/5th year (multi-series) of Elementary Education, considering training such as a construct for the re-signification of practice and the renewal of teaching. These formative meetings weredeveloped from a dialogical perspective considering the complexity of being and knowledge involving. I addition to the teacher, a resident and the students who experienced a pedagogical action based on the development of the entitled didactic sequence, Fish: from myth to food in which it was possible to dialogue the different knowledge in Science Teaching. In order to the construction of relationships between knowledge is essential for teacher and student training based on complexity, respecting the different readings of the phenomena and the variety of ways of life and culture in which the subjects are involved. Which consequently reverberates in a dialogical Science Teaching and built on the knowledge integrality.